2009
DOI: 10.1016/j.vetimm.2009.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Infection, immunity and the neuroendocrine response

Abstract: The Central Nervous (CNS) and Immune Systems (IS) are the two major adaptive systems which respond rapidly to numerous challenges that are able to compromise health. The defensive response strictly linking innate to acquired immunity, works continuously to limit pathogen invasion and damage. The efficiency of the innate response is crucial for survival and for an optimum priming of acquired immunity. During infection, the immune response is modulated by an integrated neuro-immune network which potentiates inna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 253 publications
(336 reference statements)
3
82
0
5
Order By: Relevance
“…In this study, an overall positive correlation was found between cortisol and GH but not between GH and IGF-1 plasma levels; the mean GH plasma level was lower in T1 at day 35. These observations furtherly sustain an uncoupling between the plasmatic levels of GH and IGF-1 and that the level of plasmatic GH could be mainly involved to counteract the levels of cortisol and their negative effect on metabolism and on immune efficiency in weaned piglets (Borghetti et al, 2006a(Borghetti et al, , 2006b(Borghetti et al, and 2009. In this view, the different trend in mean cortisol and GH plasma levels between groups could testify a reduction of the negative effect of stress on growth in T1.…”
Section: Discussionsupporting
confidence: 53%
“…In this study, an overall positive correlation was found between cortisol and GH but not between GH and IGF-1 plasma levels; the mean GH plasma level was lower in T1 at day 35. These observations furtherly sustain an uncoupling between the plasmatic levels of GH and IGF-1 and that the level of plasmatic GH could be mainly involved to counteract the levels of cortisol and their negative effect on metabolism and on immune efficiency in weaned piglets (Borghetti et al, 2006a(Borghetti et al, , 2006b(Borghetti et al, and 2009. In this view, the different trend in mean cortisol and GH plasma levels between groups could testify a reduction of the negative effect of stress on growth in T1.…”
Section: Discussionsupporting
confidence: 53%
“…The cellular basis of these barriers is located within the endothelial cells of the microvessels of the brain and the epithelial cells of the CP and arachnoid barrier cells (Skipor and Thiery, 2008). Some ligands of TLRs, such as LPS and poly I:C (TLR3 ligand), do not pass brain barriers; therefore, the localisation of TLRs in structures where these barriers are localised plays a key role in transferring signals from TLRs to the brain (Singh and Jiang, 2004;Borghetti et al, 2009). used in situ hybridisation techniques to provide evidence that the mRNA for TLR4 is present in the circumventricular organs, CP and leptomeninges.…”
mentioning
confidence: 99%
“…However, these increases were delayed by more than two weeks following infection and did not develop until after a peripheral parasitaemia was detected. Cytokines are fundamentally involved in the pathophysiology of the systemic inflammatory response to infection (Borghetti et al, 2009;Lewis et al, 2012). The interval between experimental B. gibsoni infection and the cytokine alterations detected in this study indicates that the systemic inflammatory response induced by experimental B. gibsoni infection, like the acute phase response, may be delayed by more than two weeks following infection.…”
Section: Accepted Manuscriptmentioning
confidence: 63%
“…Cytokines play a critical role in the initiation and M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 development of systemic inflammation and are responsible for mediating and regulating all aspects of the immune response to infection (Borghetti et al, 2009;Lewis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation